Integrating modern computing systems into the computer science curriculum at SUNY-Buffalo: a 30-year case study. (2016) - Miller, Russ
Parallel computing was introduced into the computer science curriculum at the State University of New York at Buffalo (SUNY-Buffalo) in the mid-1980s. Over the past 30 years, modern computing systems have been the focus of efforts in courses at the freshman, sophomore, junior, and senior levels, as well as at introductory and advanced graduate levels. This paper reports on the impact of these efforts, including quantitative results and inferences of courses based on modern compute systems versus traditional versions of these courses based on the sequential model of computation.